Nicknames:: a qualitative exploration into the effect of nick-names on personal histories - Bowles, Nick; Moreno, Beatriz; Psaila, Celia; Smith, Andrew (European Journal for Qualitative Research in Psychotherapy, 2009)
This piece of qualitative research explores the impact of nicknames upon the researchers. The research shows that nicknames function positively and negatively, and can either disturb contact on the Gestalt Cycle or benefit contact.  This research highlights its limitations, and suggests ways of building upon its findings.